2015
DOI: 10.3906/tar-1406-3
|View full text |Cite
|
Sign up to set email alerts
|

Moth bean germplasm screening against yellow mosaic virus, II. Developmentof moth bean high-yielding seed and fodder cultivars

Abstract: Moth bean [Vigna aconitifolia (Jacq.) Marechal] susceptibility to yellow mosaic virus (YMV) purged the crop from the farming system. Therefore, genotype-by-environment interaction (GEI) and biplot studies were undertaken to develop YMV-resistant moth bean cultivars from the germplasm. The germplasm was acquired from the National Agricultural Research Centre (NARC), Islamabad and from the farm fields in two provinces, Punjab and Sindh, Pakistan. Two different groups of moth bean genotypes were screened for YMV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…CS 1-144, UG 120133, UG 120257 and UG 120191 were among genotypes selected as resistant; while UG 130068 and UG 120170 as susceptible. Yaqoob et al (2014), working with several bean genotypes in Pakistan reported a similar ranking of genotypes across various locations.…”
Section: Discussionmentioning
confidence: 89%
“…CS 1-144, UG 120133, UG 120257 and UG 120191 were among genotypes selected as resistant; while UG 130068 and UG 120170 as susceptible. Yaqoob et al (2014), working with several bean genotypes in Pakistan reported a similar ranking of genotypes across various locations.…”
Section: Discussionmentioning
confidence: 89%